Understanding inclusion support systems: three inspiring experiences / Comprendiendo los sistemas de apoyo para la inclusión: tres experiencias inspiradoras. Issue 1 (2nd January 2019) - Rappoport, Soledad; Sandoval, Marta; Simón, Cecilia; Echeita, Gerardo
Abstract: This article presents the findings of an empirical study that aimed to gain an in-depth understanding of how inclusive support systems are configured. A qualitative case study approach was used to explore the trajectories, shared beliefs and daily practices that shape the dynamics of three educational centres recognized by external assessors for their inclusive policies and attention to diversity. The analysis carried out enabled the identification of patterns of worldviews and practices that underpin the development of sustainable inclusive school proposals, as well as an understanding of the complex interrelationship between context, resources, opportunities, threats and teaching approaches that define particular dynamics. The findings obtained help to illustrate and provide inspiration for other schools committed to defending the basic rights of all children and young people, as well as designers of educational policies and programmes.